Rapid analysis of surfactant phosphatidylcholine synthesis in preterm infants utilising the incorporation of a novel stable isotope: a pilot study. (7th June 2011) - Goss, K C W; Ledger, V; Townsend, J P; Koster, G; Hall, M; Thwaites, R; Clark, H W; Postle, A D
Abstract : While introduction of exogenous surfactant therapy has dramatically improved survival of infants born 23–28 weeks gestation, the turnover of exogenous and synthesis of endogenous surfactant components are poorly understood in this group. Additionally, up to 40% of survivors will develop neonatal chronic lung disease (nCLD), but little is known about the contribution of continued surfactant dysfunction to its cause. A variety of stable isotope incorporation methodologies have probed synthesis of phosphatidylcholine (PC), but these have a number of technical drawbacks and provide little information on individual molecular species of PC. We have monitored the incorporation of methyl -D9 choline into PC, coupled with tandem electrospray ionisation mass spectrometry (ESI-MS/MS), to quantify PC synthesis in both endotracheal aspirate (ETA) and plasma samples from preterm infants. Our methodology utilises a single infusion administration, monitors incorporation into all PC molecular species and directly reflects their synthesis and secretion. Results from six recruited infants (table 1 ) demonstrated incorporation of methyl -D9 choline into plasma PC within 6 h of administration. In contrast, negligible incorporation was detectable in ETA PC for the first 3 days, despite continued presence of un-labelled PC presumably derived from the administered exogenous surfactant. PC synthesis subsequently increased and was maintained for a prolonged period. This pilot study has demonstrated that infusion of methyl -D9 choline, coupled with ESI-MS/MS analysis of plasma and ETA samples, is a safe and rapid method of monitoring PC production in both the liver and lung of preterm infants at risk of developing nCLD.